High genetic diversity revealed in the native populations of Undaria pinnatifida from China by mitochondrial sequences and nuclear microsatellites - Li, Yuqian; Shan, Tifeng; Pang, Shaojun (Frontiers in Marine Science, 2023)
According to historical documents, China has its own native Undaria pinnatifida populations in Zhejiang and Fujian provinces, and they are potentially valuable breeding materials for this economically important kelp. However, their distribution range has been declining northward and we cannot find it now in Fujian province and southern Zhejiang province. They are currently confirmed to be distributed only on some small islands distant from the mainland, likely facing the anthropogenic threats such as habitat deterioration and marine heatwave. Thus, they are of conservation concern. Herein, we used the mitochondrial sequences of cox3 and tatC–tLeu regions, and 10 nuclear microsatellites to analyze the genetic diversity and genetic structure of three temporal populations from Gouqi Island and one population from Yushan Island. A total of eight haplotypes of the combined cox3 and tatC–tLeu sequences were identified with five of them being unique in these populations. Based on microsatellites, we estimated a minimum expected heterozygosity of 0.671 and a minimum effective number of alleles of 5.3 within each population, and revealed shallow genetic structure among populations by Bayesian model-based STRUCTURE analysis and low Fst values. We did not detect signs of recent bottleneck in all populations. The high genetic diversity identified in the southern native populations will provide an advantageous basis for them to adapt to the future environmental changes. A thorough field survey about the detailed distribution of the native populations is needed in order to estimate their population size and better protect the natural resources of this important alga.